Ewangelia według św. Łukasza jako przykład starożytnej historiografii - Kucharek, Dariusz (Warszawskie Studia Teologiczne, 2024)
The article presents the work of the Evangelist Luke and his person in the context of ancient historiography, shows typical elements of ancient historical works, and shows the author as an outstanding historian of antiquity. The key to these statements is the comparison of selected elements of Luke’s Gospel and outstanding historical works of ancient authors such as: Thucydides, Flavius Arrian, Velleius Paterculus, Herodotus, Xenophon, Flavius Josephus, Herodian